On A Certain Class of Meromorphic Multivalent Functions Defined by Fractional Calculus Operator - Hussein, Adnan Aziz; Jassim, Kassim Abdul Hameed (Iraqi Journal of Science, 2019)
In this work, we study a new class of meromorphicmultivalent functions, defined by fractional differ-integral operator.We obtain some geometricproperties, such ascoefficient inequality, growth and distortion bounds, convolution properties, integral representation, radii of starlikeness, convexity, extreme pointsproperties, weighted mean and arithmetic meanproperties.